Characterization of three lamp genes from largemouth bass (Micropterus salmoides): molecular cloning, expression patterns, and their transcriptional levels in response to fast and refeeding strategy - Yang, Yan-Lin; Zeng, Wan-Hong; Peng, Yong; Zuo, Shi-Yu; Fu, Yuan-Qi; Xiao, Yi-Ming; Huang, Wen-Li; Wen, Zheng-Yong; Hu, Wei; Yang, Yu-Ying; Huang, Xiao-Feng (Frontiers in Physiology, 2024)
Lysosomes-associated membrane proteins (LampsLAMPs), a family of glycosylated proteins and major constituents of the lysosomal membranes, play a dominant role in various cellular processes, including phagocytosis, autophagy and immunity in mammals. However, their roles in aquatic species remain poorly known.In the present study, three lamp genes were cloned and characterized from Micropterus salmoides. Subsequently, their transcriptional levels in response to different nutritional status were investigated. The full-length coding sequences of lamp1, lamp2 and lamp3 were 1251bp, 1224bp and 771bp, encoding 416, 407 and 256 amino acids, respectively.Multiple sequence alignment showed that lamp1LAMP1-3 were highly conserved among the different fish species, respectively. 3-D structure prediction, genomic survey, and phylogenetic analysis were further confirmed that these genes are widely existed in vertebrates. The mRNA expression of the three genes was ubiquitously expressed in all selected tissues, including liver, brain, gill, heart, muscle, spleen, kidney, stomach, adipose and intestine, lamp1, lamp2 and lamp3 showsed highly transcript levels in brain and muscle,; lamp2 displays highly expression level in heart, muscle and spleen, ; but lamp3 shows highly transcript level in spleen, liver and kidney, respectively. To analyze the function of the three genes under starvation stress in largemouth bass, three experimental treatment groups (fasted group and refeeding group, control group) were established in the current study. The results indicated that the expression of lamp1 was significant induced after starvation, and then returned to normal levels after refeeding in the liver. The expression of lamp2 and lamp3 exhibited the same trend in the liver.In addition, in the spleen and the kidney, the transcript level of lamp1 and lamp2 was remarkably increased in the fasted treatment group and slightly decreased in the refed treatment group, respectively. Collectively,ing, our findings suggest that three lamp genes mayight have differential function in the immune and energetic organism in largemouth bass, which is helpful in understanding roles of lamps in aquatic species.